Paleogeographic Reconstruction of Precambrian Terranes Reworked by Phanerozoic Orogens: An Example Based on Detrital Zircon REE From Lhasa Terrane in Southern Tibet - Hu, Pei‐yuan; Zhai, Qing‐guo; Cawood, Peter A.; Weinberg, Roberto F.; Zhao, Guo‐chun; Tang, Yue; Liu, Yi‐ming (Geophysical research letters, 2023)
Paleogeographic reconstruction of Precambrian terranes reworked by Phanerozoic orogens (e.g., the Tibetan Plateau) results in complex lithotectonic relations due to intracrustal reworking by tectonothermal events. Detrital zircon rare earth element (REE) databases at global (global major river sands) and regional (the Gangdese Mountains, southern Tibet) scales reveal trends in LREEN‾/HREEN‾ $\overline{{\mathrm{L}\mathrm{R}\mathrm{E}\mathrm{E}}_{\mathrm{N}}}/\overline{{\mathrm{H}\mathrm{R}\mathrm{E}\mathrm{E}}_{\mathrm{N}}}$ and Eu/Eu* that effectively record the crustal evolution of the source, including crustal thickness and redox state of the magma that generated the zircons. Regional comparisons of these chemical markers provide a new approach for paleogeographic reconstructions that we apply to study the origin of the Lhasa terrane, southern Tibet. Using Precambrian to early Paleozoic sedimentary and igneous rocks in the Lhasa terrane and compiling detrital zircon analyses from the northern margin of Gondwana, we show that the Lhasa terrane had an African affinity in the Rodinia–Gondwana supercontinent cycles (ca. 1.4–0.4 Ga). Plain Language Summary Constraining the paleogeographic positions and affinities of continental fragments plays a crucial role in validating the concept of the supercontinent cycle. However, tracking the evolving paleogeographic position of these fragments, especially for those of Precambrian age, has proven difficult. We explore the potential for solving this problem by using detrital zircon rare earth element (REE) abundances, which are controlled by the magma source depth, protolith type, oxygen fugacity, and magmatic water content of parental melts. We reveal correlations between detrital zircon REE abundances and crustal evolution in different tectonic settings based on global and regional detrital zircon databases. We subsequently demonstrate how detrital zircon REE abundances show that the Lhasa terrane in the southern Tibet is a fragment derived from Africa. Our study provides a new perspective on the paleogeographic reconstruction of continental fragments through Earth's history and thus has important implications for supercontinent research. Key Points Zircon rare earth element (REE) abundances reflect the composition of, and the conditions that generated, the parental melts Trends in detrital zircon REE effectively preserve a crustal evolution history and provide a new approach for paleogeographic reconstruction The Lhasa terrane in the southern Tibet had an African affinity in the Rodinia‐Gondwana supercontinent cycles